THE ROLE OF LEADERSHIP AND CULTURE IN SHAPING EMPLOYEE PERFORMANCE: A COMMITMENT PERSPECTIVE - Athoillah, Athoillah; Dwiarti, Witri (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2025)
This research aims to analyze the influence of transformational leadership style and organizational culture on employee performance and examine the role of organizational commitment in mediating the impact of transformational leadership style and organizational culture on employee performance. The method used is quantitative with Structural Equation Model-Partial Least Square (SEM-PLS) analysis using the SmartPLS 4.1.0.9 program for data processing. The respondents in this research consisted of 139 employees, and the sampling technique was simple random sampling. The results of this study indicate that transformational leadership style does not significantly affect employee performance. Organizational culture and organizational commitment have a significant effect on employee performance. Organizational commitment can mediate the influence of transformational leadership style and organizational culture on employee performance.